Acid chlorides prepn. from organic acids and phosgene - with a hexa-alkyl phosphorotriamide catalyst at elevated temp - JULIEN CYRILLE MAURICE DEWEERDT ET BERNARD ROBERT-COLOMBY (1977)
Prodn. of acid chlorides by heating COCl2 with organic acids in the presence, as catalyst, of a phosphoric acid triamide of formula O=P- N(R)2- -3 (where each R is 1-4 C alkyl). The pref. catalyst is hexamethylphosphotriamide. The reaction is pref. performed at 100-150 degrees C using 1-5 mol % of catalyst (based on the organic acid) e.g. 2,2-di-Me-propionic or 3,5,5-tri-Me-hexanoic. The prod. may be sepd. by distn. from the catalyst which is pref. recycled to a new reaction. Acid chlorides are useful intermediates in organic syntheses. The difference in b.pt. between the catalysts and acid chlorides allows a simple sepn. and the catalyst remains active after several successive reactions.